EXTENT OF ADOPTION OF RECOMMENDED PRODUCTION TECHNOLOGY FOR GROUNDNUT CULTIVATION - CHAND, SUBHASH (Annals of Agricultural Research, 2014)
The extent of adoption was conceived as a degree to which a particular recommended practice of groundnut cultivation was practiced by the respondents. Majority of the respondent (57%) were medium adopters, followed by low adopters (28%) and a small percentage (15%) of the respondents as high adopters of recommended production technology of groundnut. The maximum or high adoption of recommended production technology of groundnut cultivation was found in the practice like seed rate, spacing, depth of sowing and irrigation application. While the fertilizer application, use of plant protection measures and of HYV seeds were found least adopted by farmers.